"That Which is Administered is Best": The Federalists and Anti-Federalists on Form - Pino, Jordan (Colloquium: The Political Science Journal of Boston College, 2017)
In this short thought-piece, I suggest a particular way of understanding the nature of the debate between the Federalists and the Anti-Federalists with respect to the form of the United States’ government. Namely, I contend that this debate is best understood as a division between first and second principles, a disagreement about the validity of Alexander Pope’s maxim: “that which is best administered is best.” Through this lens, Federalist concern to promote a particular end of government overtakes concern to retain the federal structure of government under the Articles of Confederation, the latter a secondary characteristic to men such as John Adams and Alexander Hamilton. On the opposite side, Anti-Federalists prized the league of separate and sovereign republics with a primary attachment, due in part to the localism thesis that individuals such as The Federal Farmer endorsed: government that is nearby can be controlled. I argue that the Federalists comprehended the revolutionary moment as one in which a great nation could be formed; the Anti-Federalists were more attuned to protecting the various liberties of the people. These primary attachments led to diverging secondary considerations about the form of the national authority.